HUBUNGAN PENGETAHUAN, SIKAP DAN MOTIVASI DENGAN PERSEPSI KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJA DI PT TIGA MUSTIKA AGUNG DI KABUPATEN MUARA BUNGO TAHUN 2021 - Muammar Khadafi; Entianopa Entianopa; Hamdani Hamdani (Jurnal Cakrawala Ilmiah, 2023)
Data from the Central Social Security Agency for 2021 shows the number of work accidents in the forestry sector is 20.7%. If a person's perception of risk is bad, then the behavior that arises tends to ignore the risk exposure. There were 16 work accidents at PT Tiga Mustika Agung in 2020. This study aims to determine the factors associated with the perception of occupational safety and health in workers at PT Tiga Mustika Agung. The research design was cross sectional. The study was conducted at PT Tiga Mustika Agung on January 24 to 30, 2022. The research population was all 100 employees at PT Tiga Mustika Agung, while the research sample was 50 employees at PT Tiga Mustika Agung. Samples were taken by simple random sampling technique. The research instrument is a questionnaire. Data were analyzed by chi-square test. The results showed that 46.0% of respondents had poor OHS perceptions, 54.0% of respondents had poor knowledge, 46.0% of respondents had poor attitudes and 38.0% of respondents had poor motivation. The results of statistical tests showed that there was a relationship between knowledge (p=0.020) and attitude (p=0.005) with perceptions of occupational safety and health. There is no relationship between motivation and perceptions of occupational safety and health (p-value=0.888). It is expected that the company will provide training to workers on occupational safety and health and provide personal protective equipment to workers and supervise the use of personal protective equipment.